Le maintien en emploi du salarié handicapé : effets et limites de l’obligation d’accommodement raisonnable en droit québécois - Anne-Marie Laflamme (Perspectives Interdisciplinaires sur le Travail et la Santé)
In the province of Québec, the right to reasonable accommodation, the corollary of the right to equality established under the charters of human rights, has taken such a dimension that it provides disabled employees with true protection with respect to maintenance of the employment relationship. In the first part of this paper, the author exposes the paradigm shift resulting from this evolution in case law, and defines the parameters of the right to reasonable accommodation that the employer must respect for employees unable to perform their duties due to their medical status. The author then emphasizes that this change has occurred outside the industrial accidents and occupational diseases compensation plan. Moreover, this exclusive regime, innovative at the time of its adoption, has become, in some respects, disadvantageous for employees with an employment injury, at least with regard to maintaining the employment relationship.